Performance of the Environmental Service in Handling Garbage Piles in Baleendah District, Bandung Regency - Fidowaty, Tatik; Firdaus, Julian Maulana Jafar (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
The purpose of this study was to determine the performance of the Environmental Agency in addressing the piles of waste in Baleendah District, Bandung Regency. The large population of Baleendah District naturally impacts the volume of waste generated each day. This waste is not properly collected, resulting in a buildup. This research employed a descriptive method with a qualitative approach. Interviews were conducted with officials using purposive techniques, while interviews with the public were conducted using accidental techniques. Additionally, the researchers conducted literature studies and observations with the government and the public. The results showed that the amount of expenditure was not offset by the amount of waste collected, resulting in a buildup. Officials have good skills in sorting waste for economic value, but this is still not matched by their responsiveness in collecting waste. This is due to late waste collection schedules and the continued indiscriminate littering by the community.